2021
DOI: 10.32535/jicp.v4i1.1132
|View full text |Cite
|
Sign up to set email alerts
|

Development of Safety Plan Building Based on Work Breakdown Structure (WBS) in Campus Area of UI Depok to Reduce Work Accident

Abstract: There is very little discussion about the needs of occupational health within the University area. In fact, the University is a place where interaction occurs not only for lecturers and students, but also employees, contractors and other visitors with very varied backgrounds and cultures. The lack of application of OHSMS in the construction sector in the University area causes a high number of work accidents. Making a safety plan at the initiation stage can reduce and prevent potential hazards that will occur.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Gambatese et al (2005) stated that design for construction safety includes handling the safety of construction workers in a permanent design on a project. It can be concluded that considering safety in the design stage is very important in construction and hence the design concept for construction safety has been officially proposed in the global construction research agenda (Lestari, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Gambatese et al (2005) stated that design for construction safety includes handling the safety of construction workers in a permanent design on a project. It can be concluded that considering safety in the design stage is very important in construction and hence the design concept for construction safety has been officially proposed in the global construction research agenda (Lestari, 2021).…”
Section: Introductionmentioning
confidence: 99%